ETHNIC SPECIFICS OF THE MAIN CARDIOVASCULAR RISK FACTORS PREVALENCE AMONG RURAL INHABITANTS OF A RUSSIAN REGION AND REGIONS OF KYRGYZSTAN AND KAZAKHSTAN - A. V. Kontsevaya; A. O. Myrzamatova А; A. G. Polupanov; K. A. Alikhanova; A. K. Kashirin; A. N. Khalmatov; A. T. Altymysheva; E. B. Iskakov; Yu. A. Balanova; A. S. Dzhumagulova (Российский кардиологический журнал, 2017)
Aim. To investigate on the prevalence of the main cardiovascular RF among inhabitants of rural regions in three countries: Russia, Kyrgyzstan, Kazakhstan, with the analysis of ethnic specifics (by the data from Interepid study).Material and methods. The study has been conducted under the framework of international project “Interepid”. Into analysis, the representative selections included, of rural inhabitants from Volga district of Samara Region of Russia (n=1050), from Chuysky Region of Kyrgyzstan Republic (n=1341) and Karaganda Region of Kazakhstan Republic (n=1807), age 25-64 y. o. Under the framework of “Interepid”, the investigation included questionnaires by special chart, objective data and laboratory tests. Smoking was set if at least one cigarette per day. Arterial hypertension was set by criteria of increased BP and in normal BP if on treatment. Obesity criteria: body mass index ≥30 kg/m2 as body mass in kilograms divided by height in meters squared.Results. Among the three analyzed countries, smoking was most prevalent in the Russians in Kazakhstan, and the lowest — in Russia. Russian men smoked more commonly comparing to native inhabitants in Kazakhstan, as in Kyrgyzstan. Arterial hypertension prevalence in the five analyzed groups showed the most prevalence among Russian population in Kyrgyzstan. In Kazakhstan and Kyrgyzstan, among men the mean SBP values were significantly higher in Russians. Obesity was the most prevalent among rural inhabitants of Kyrgyzstan, among men and women of  Kyrgyz nationality, and the peak of this parameter was at 50-59 y. o.; obesity prevalence declined after 60 y. o. Conclusion. There remains high prevalence of CVD risk factors on the postsoviet area. The data obtained, points on ethnic differences of the main CVD risk factors inside the countries. It was shown that at populational level the Russians, living in rural areas of Middle Asia countries have more risk factors comparing to the Russians living in Russia (Samarskaya Region).